POTENTIAL OF SEVERAL WEEDS AS COVER CROP ON MATURE OIL PALM AREA - Asbur, Yenni; Rambe, Rahmi Dwi Handayani; Purwaningrum, Yayuk; Kusbiantoro, Dedi (Jurnal Penelitian Kelapa Sawit, 2018)
Cover crop management in oil palm plantation is one of techniques to conserve soil and water in oil palm plantation. This research was aimed to study potential of several weeds as cover crops on mature oil palm plantation area. The research was conducted in an 20 year-old oil palm plantation in Namorambe, Deli Serdang, North Sumatra from March to June 2017. The research was arranged using non factorial Randomized Block Design. Four species of weeds (N. biserrata, A. gangetica, P. conjugatum, and A. conyzoides) were employed as treatments, every treatment was replicated three times. The results showed that N. biserrata, A. gangetica, P. conjugatum, and A. conyzoides were potential to be used as cover crops on mature oil palm area. These species were easily propagated, covered area rapidly (8-12 weeks after planting), produced abundant leaves and branches, and contained nutrients in the plant tissues. The highest content of N, P, K, and organic C was identified in N. biserrata (4,02% N), P. conjugatum (0,31% P), A. gangetica (2,41% K), dan A. conyzoides (37,23% organic C).